Struktur Komunitas Gastropoda Di Perairan Pesisir Kecamatan Genuk Kota Semarang - Nugroho, Krisna Dwi; Suryono, Chrisna Adhi; Irwani, Irwani (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Gastropods have an important role in aquatic environments, especially in food and energy cycles. This aim of study determine the abundance and structure community of gastropods and physical parameters of the water, the type of substrate sediments and organic matter content in sediments that serve to optimize the utilization analysis and estimation of the abundance of gastropods conditions contained in the Genuk Coastal Waters, the city of Semarang. The method used in this research descriptive method by means of sampling stations gastropods includes 6 points. The study results for all sampling points had 260 individuals, that comprise of 10 species, namely Turricula javana, Thaislacera, Murex trapa, Bufonaria rana linnaeus, Nassarius sp, Natica tigrina, Babylonia spirata, Turritella terebra, Pseudoneptunea varicosa, and Conus sp. Sum abundance of species ranging between 0,08 to 2,37 individu/m2. Value index of diversity (H') ranged from 0,000 to 2,026 in the category of low and moderate, and values of uniformity index (e) ranged from 0,000 to 1,461 are included in the high category and the dominance index (c) between 0,255 to 1 in the category of not no dominance (TAD) and no dominance (AD), and for the distribution patterns are dominated by the uniform distribution pattern from the clumped distribution patterns whereas community similarity (S) category was up to the height ranges between 44,44% - 88,89%.